Dark places - Flynn, Gillian 1971- (Concorde, 2016)
Libby Day was only seven years old when her mother and two sisters were murdered and her brother Ben was jailed for the crime. Now, twenty-five years later, Libby discovers shocking evidence that Ben may be innocent, and the real killer still at large